A new record of an ant – like Salticid Spider, Myrmarachne kiboschensis Lassert, 1925 from Manipur, India - Kananbala, A; Bhubaneshwari, M; Manoj, K; Siliwal, Manju (Journal of Experimental Sciences, 2012)
An ant-like Salticid spider, Myrmarachne kiboschensis Lassert, 1925 was first recorded from Manipur, India